Marketing channel selection by smallholder farmers - Arinloye, D.A.; Pascucci, S.; Linnemann, A.; Coulibaly, O.; Hagelaar, G.; Omta, O.S. (Informa UK Limited, 2015)
This article aims at analyzing Beninese smallholder famers’ selection of high value markets, such as export and processing-oriented marketing channels, in the pineapple supply chain. Four main marketing channels were investigated: rural, urban, and export fresh pineapple markets and processing-oriented markets. Primary data collected from 285 pineapple farmers through a field survey in different locations in South Benin were used to analyze simultaneous selection of multiple channels. A multivariate probit approach has been used in our empirical strategy. Farmers’ characteristics, production systems features, quality attributes, and types of marketing context have been used as main explanatory variables. Results indicate the Beninese pineapple farmers select market channels with high values when they have the expertise and know-how for coping and complying with quality issues.